Ré-habiter la Terre. Cinquante ans d’utopies biorégionalistes - Paolo Stuppia (Développement Durable et Territoires)
This article aims to expose to a French public the main Bioregional theories, history, and some of its achievements. Indeed, this radical environmental movement was created 50 years ago in the US, but it only starts to be known in France nowadays. In line with its countercultural origins, Bioregionalism seeks a transition to local alternatives. This final goal is inseparable from experimentation at every stage of the process, from the definition of boundaries of a bioregion to the efforts to restore its specific ecosystem, or even to determine the best ways to (self-)govern its territory. Two examples of Bioregional practices complete these reflections.